2016
DOI: 10.1371/journal.pone.0167707
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Milk Protein Supplementation with Moderate Physical Activity Improves Locomotion Function in Aging Rats

Abstract: Aging is associated with a loss of muscle mass and functional capacity. Present study was designed to compare the impact of specific dairy proteins on muscular function with or without a low-intensity physical activity program on a treadmill in an aged rat model. We investigated the effects of nutritional supplementation, five days a week over a 2-month period with a slow digestible protein, casein or fast digestible proteins, whey or soluble milk protein, on strength and locomotor parameters in sedentary or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…According to the current data, several reports showed that aging caused a reduction in physical activity, including locomotor activity in a novel environment in rodents and humans (Ayers & Verghese, ; Ingram & Jucker, ; Lafoux, Baudry, Bonhomme, Ruyet, & Huchet, ; Yu, Xu, Song, Ji, & Zhang, ). Additionally, some reports have suggested a reduction in spinogenesis and in dendritic length in aged animals (Alcántara‐González et al, , ; Cabrera‐Pedraza et al, ; Diaz et al, ; Hernández‐Hernández et al, ; Juárez et al, ; Sánchez et al, ; Solis‐Gaspar, Vazquez‐Roque, Jesús Gómez‐Villalobos, & Flores, ; Vidal et al, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…According to the current data, several reports showed that aging caused a reduction in physical activity, including locomotor activity in a novel environment in rodents and humans (Ayers & Verghese, ; Ingram & Jucker, ; Lafoux, Baudry, Bonhomme, Ruyet, & Huchet, ; Yu, Xu, Song, Ji, & Zhang, ). Additionally, some reports have suggested a reduction in spinogenesis and in dendritic length in aged animals (Alcántara‐González et al, , ; Cabrera‐Pedraza et al, ; Diaz et al, ; Hernández‐Hernández et al, ; Juárez et al, ; Sánchez et al, ; Solis‐Gaspar, Vazquez‐Roque, Jesús Gómez‐Villalobos, & Flores, ; Vidal et al, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 51%
“…As we mention before, it is well known that aged rats show a reduction in physical activity, including locomotor activity in a novel environment (Ingram & Jucker, ; Lafoux et al, ; Yu et al, ). Accordingly, an increase in locomotor activity in a novel environment may suggest a behavioral improvement.…”
Section: Discussionmentioning
confidence: 81%
“…The present study demonstrated that after seven days of immobilization, muscle disuse promoted significant atrophy of muscle tissue, both in adult (five months) and elderly animals (15 months), 3,10 and that exercise was able to reverse this harmful effect in a seven day exercise intervention in adult animals, however in the elderly animals, seven days of exercise were not enough to reverse the process of muscle atrophy.…”
Section: Discussionmentioning
confidence: 49%
“…Previous reports have shown that aging caused a reduction in locomotor activity (Flores‐Vivaldo et al., 2019; Insgrama & Jucker, 1999; Lafoux, Baudry, Bonhomme, Le Ruyet, & Huchet, 2016; Yu, Xu, Song, Ji, & Zhang, 2013). For this reason, we analyzed whether the PBA has an effect on this type of behavior.…”
Section: Resultsmentioning
confidence: 95%
“…This cognitive improvement was not related to an increase in locomotor activity in a new environment. It is also well‐known that, like cognition, locomotive activity is also reduced with aging (Alcantara‐González et al, 2012; Flores‐Vivaldo et al., 2019; Insgrama & Jucker, 1999; Lafoux et al., 2016; Yu et al., 2013). However, our results suggest that the PBA did not modify locomotive activity in a novel environment in the old mice, despite producing an improvement in the number of dendritic spines and markers for synaptophysin without changes in the total dendritic length in the NAcc, a structure related to this behavior.…”
Section: Discussionmentioning
confidence: 99%